Perspectives of substitute decision‐makers and staff about person‐centred physical activity in long‐term care. - Chu, Charlene H.; Quan, Amanda M. L.; Gandhi, Freya; McGilton, Katherine S. (Health Expectations, 2022)
Introduction: This paper aims to explore the care processes that best exemplify person‐centred care during physical activity (PA) for long‐term care (LTC) residents with dementia from the perspectives of substitute decision‐makers (SDMs) and LTC home staff. Little is known about how person‐centred care is reflected during PA for residents with dementia, or the barriers and benefits to enacting person‐centred care during PA. Methods: Semistructured interviews were used to collect SDMs and LTC home staffs' perspectives on the importance of person‐centred care during PA from two LTC homes in Canada. The McCormack and McCance person‐centredness framework was used to guide thematic content analysis of responses. Results: SDM (n = 26) and staff (n = 21) identified actions categorized under the sympathetic presence or engagement care processes from the person‐centredness framework as most reflecting person‐centred care. Benefits of person‐centred care during PA were categorized into three themes: functional and physical, behavioural and communication and psychosocial improvements. Barriers to person‐centred care during PA identified were lack of time, opportunities for meaningful activity in LTC setting and staff experiences with resident aggression. Significance: Understanding the care processes that are most recognized as person‐centred care and valued by SDMs and LTC home staff has implications for education and training. Insights into SDMs' care expectations regarding person‐centred care can inform staff about which actions should be prioritized to meet care expectations and can foster relationships to the benefit of residents with dementia. Patient and Public Contribution: Study participants were not involved in the development of research questions, research design or outcome measures of this study.